ADOPTION OF TOMATO POST – HARVEST VALUE ADDITION TECHNOLOGIES (TPVTS) AND WELL-BEING OF TIV RURAL FARMERS IN BENUE STATE, NIGERIA - Beeior, C.T.; Akpehe, G.A.; Wegh, S.F.; Odiaka, E.C.; Igbanyam, C. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated the adoption of tomato postharvest value addition technologies and well-being of rural farmers in Benue State. A sample size of 400 farmers was selected from six major tomato-producing Local Government Areas of Tiv rural farmers using cluster, purposive, and random sampling techniques. Data was collected through semi-structured interviews and focus group discussions, and analyzed using descriptive and inferential statistics. The results showed a significant increase in farmers' average annual income after adopting improved TPVTs, from ₦31,465.34 to ₦75,697.92. This increase in income enhanced their purchasing power, access to basic necessities, and overall well-being. The study concluded that the high adoption rate of TPVTs among rural farmers has improved their well-being and the rural economy. Recommendations include scaling up TPVTs to all tomato farmers, infrastructural development, and adequate funding to support effective adoption among rural farmers.